Recovery of nickel and cobalt from battery black powder
By using a slag system rich in MnO and Li2O in the pyrometallurgy process, the slag composition and temperature are controlled, and the problem of corrosion of magnesium refractory bricks at high temperatures is solved, the furnace life is extended and the recovery efficiency of Ni and Co is improved.
Patent Information
- Application Number
- CN202380040221.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-05-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-05-08
AI Technical Summary
When the existing pyrometallurgical process recovers Ni and Co in Li ion batteries at high temperatures, it leads to wear and corrosion of the furnace wall, resulting in high maintenance costs and short furnace life, especially the magnesium material of refractory bricks is easily dissolved at high temperatures.
The slag system rich in MnO and Li2O is used for pyrometallurgy. By controlling the composition of the slag, especially the MnO content is between 25% and 70%, combined with an appropriate amount of Al2O3, SiO2, CaO and P2O5, it forms a low melting point and high flow. The corrosion of magnesium refractory bricks is inhibited and the content of compounds not derived from Li ion batteries is reduced by optimizing flux and feed.
It significantly reduces the wear of magnesium refractory bricks, extends the service life of the furnace, reduces maintenance costs, and improves the recycling efficiency of Ni and Co, ensuring the stability of the slag and low-cost production.
Smart Images

Figure BDA0005131972810000151 
Figure BDA0005131972810000161 
Figure BDA0005131972810000171
Abstract
Description
[0001] The present invention belongs to the field of pyrometallurgy and relates to the recovery of Ni and Co from Li-ion batteries or their waste, more particularly from battery black powder.
[0002] In recent years, especially driven by new regulations in Europe and China, electric vehicles have experienced unprecedented growth, which are designed to gradually reduce the CO2 footprint of automobiles and limit urban air pollution. This growth is expected to continue in the next few decades. The adoption of electric vehicles depends largely on the performance of the batteries used to store electrical energy. In order to obtain the highest energy density while keeping costs under control, rechargeable Li-ion batteries are preferably selected. Many of these batteries contain positive electrodes based on the transition metals Ni, Mn and Co, and are therefore also called NMC batteries. As the electric vehicle market grows, the demand for these metals is expected to increase significantly.
[0003] The demand for Ni and Co may even exceed global production capacity. Co is particularly critical because it is currently only produced as a by-product of the Ni and Cu industries. The nickel market is significantly larger than the cobalt market. Most of the Ni is used to produce stainless steel, where the purity of Ni is less important. However, high-purity Ni and high-purity Co metals or compounds are already in short supply. In view of the above, the recovery of Ni and Co from spent Li-ion batteries or their waste is an attractive proposition, which is also known as the battery circular economy.
[0004] In particular, so-called "battery black" (BM) or "black matter" is a very interesting starting material for recycling. Although the expression battery black is often used in industry, the exact composition can vary significantly, depending on the manufacturer or application. Usually, scrapped batteries are disassembled and shredded, which may include separating the casing material, foil and / or the negative electrode. Sometimes they are also pre-treated. Compared to the processing of complete batteries, the battery black resulting from this process is usually characterized by a relatively low aluminum content. On the other hand, it contains considerable amounts of lithium, manganese, cobalt and / or nickel.
[0005] Facilities for recycling batteries and battery waste typically process battery black powder using hydrometallurgical processes to produce salts or metal hydroxides. Pyrometallurgical refining processes are less common, and the combined pyro-hydrometallurgical process according to the present invention remains a rare exception.
[0006] The known pyrometallurgical process for recycling Li-ion batteries reduces the oxides of nickel, cobalt and copper to their respective metals in a furnace and concentrates them in an alloy phase at high temperatures. Other compounds such as lithium and manganese are oxidized to Li2O and MnO and collected in the slag.
[0007] Over time, running such a high temperature process can cause wear or corrosion of the furnace walls. Typically, the furnace walls are made of refractory bricks. The most commonly used bricks are based on magnesia. Typical magnesia bricks contain over 90% magnesia, while magnesia-chrome bricks contain 50% to 70%. It has been observed that the magnesia is dissolved by normal slag during furnace operation. This wear or corrosion is a recurring problem, resulting in high maintenance costs, as the furnace needs to be shut down and the refractory bricks need to be replaced regularly. This problem becomes more pronounced at higher operating temperatures, for example above 1550°C.
[0008] Therefore, the object of the present invention is not only to provide an efficient method for recovering Ni and Co from Li-ion batteries or their waste, in particular from battery black powder, but also to increase the life of the furnace. This is achieved by operating with a dedicated MnO and Li2O-rich slag system with a controlled composition aimed at limiting the corrosion of Mg-containing refractory bricks.
[0009] WO2017121663 describes the composition of slag produced in an industrial process and discloses the effect of MnO on slag viscosity and cobalt recovery. The main slag components described therein are CaO, SiO2, Al2O3, Li2O and MnO or MnO2. The MnO concentration in those slags disclosed is very low and the teaching is limited to the amount of MnO in the slag.
[0010] Wittkowski et al. (Speciation of Manganese in a Synthetic Recycling Slag Relevant for LithiumRecycling from Lithium-Ion Batteries: Metals, Vol. 11(2), 2021, p. 188) analyzed the phase composition of different Li-containing slags relevant for Li-ion battery recycling. Battery black powder is not mentioned as a starting material. All reported slags are characterized by MnO contents much lower than those according to the present invention.
[0011] On the other hand, recent Li-ion batteries generally contain increased amounts of Mn. This results in slag compositions having higher MnO contents.
[0012] WO12140951, WO13080266 and WO20013294 propose methods for recycling Li-ion battery waste to recover Ni and Co while fixing impurities such as Fe and P in the slag phase. Although it is stated that Mn may be a component of the obtained slag, no preferred range or specific effect of MnO in such slag is specified.
[0013] CN103924088 and EP3269832 describe a molten bath smelting process of spent batteries, producing alloys containing Co and / or Ni and slags rich in SiO2 and MnO. There is no mention of the Li content in these slags, nor any effect of MnO or Li2O. There is no mention of battery black powder as a starting material.
[0014] CN105838895 and Xiao et al. (Recovery of Valuable Metals from Spent Lithium-Ion Batteries by Smelting Reduction Process Based on MnO-SiO2-Al2O3 Slag System: J. Sustain. Metall., Vol. 3, 2017, pp. 703-710) describe the composition of slag produced by smelting Li-ion batteries and the leaching process for extracting Li and Mn from the resulting slag. A method for extracting lithium and manganese from lithium-containing manganese-rich slag is disclosed without discussing the specific slag properties. In all examples given, the typical slag is rich in MnO, SiO2 and Al2O3, while the content of Li2O is quite low.
[0015] Vest et al. (Slag design for lithium recovery from spent batteries: Int. Work. Met. Interact., Vol. 9(93), 2010, pp. 93-106) describe theoretical calculations for different slag systems, some of which are also rich in MnO. However, with regard to lithium, the goal is to design a slag so that the Li distribution shifts towards the maximum concentration in the flue dust rather than in the slag. Therefore, one of the desired slag properties is a low capacity / solubility for Li2O.
[0016] EP21176046 describes a pyrometallurgical recycling process for Li-ion batteries, in which the batteries are fed into a smelting furnace equipped with means for submerging and injecting an O2-containing gas to reduce most of the Ni and Co. The slag obtained is treated in a second reduction smelting step, in which the remaining Ni and Co are extracted. The slag contains less than 20% MnO, with higher amounts of Al2O3, such as above 20% or even above 30%. No mention is made of wear or corrosion of the furnace walls.
[0017] The present invention achieves a significant reduction in the wear of magnesia-containing refractory bricks in a pyrometallurgical process, which contributes to the overall economy of the process of the present invention. The following embodiments further describe the present invention.
[0018] According to a first embodiment, a method for recovering Ni and Co from Li-ion batteries or waste thereof comprises the following steps:
[0019] - Providing a furnace lined with magnesia-containing refractory bricks;
[0020] - providing a feed comprising a slag forming agent and Li-ion batteries or waste thereof, wherein the Al content of the feed is less than 8%; and
[0021] - Smelting the feed material under reducing conditions to obtain an alloy containing a major portion of Ni and Co and a slag containing Li, wherein the slag has the following mass composition percentages:
[0022] 25% <MnO<70%;
[0023] Al2O3+0.5MnO<45%;
[0024] SiO2>5%;
[0025] Li2O>1%;
[0026] 0.5% <P2O5<10%;
[0027] MnO+Li2O+Al2O3+CaO+SiO2+FeO+MgO+P2O5>90%; and
[0028] Among them, (CaO+2Li2O+0.4MnO) / SiO2≥2.0.
[0029] "Slag former" means, for example, one or more of CaO, Al2O3 and SiO2. Other slag formers well known to the skilled person may also be present. The slag former compounds themselves may be added, or they may be obtained in situ from readily oxidizable metals present in the feed, such as aluminum.
[0030] "Furnace lined with magnesia-containing refractory bricks" refers to a metallurgical furnace which is at least partially lined with such bricks, in particular in the areas which come into contact with the slag.
[0031] While the method is suitable for processing Li-ion batteries or their waste, other materials may also be included in the metallurgical feed. For example, a mixed hydroxide precipitate (MHP) may be added: this product typically contains useful concentrations of Co, Ni and Mn as well as Mg. The Co and Ni are recovered in the alloy, while the Mn and Mg are lost in the slag, where they play a useful role in protecting the lining. Combining battery materials with MHP also optimizes the overall energy consumption, since during the smelting process, batteries tend to be exothermic, while MHP is endothermic. The total feed may advantageously contain up to 30% by weight of MHP.
[0032] In the total feed, compounds other than MHP not originating from Li-ion batteries or their waste should preferably be limited to less than 25%, more preferably less than 15%.
[0033] According to another embodiment, the Li-ion battery or its waste is battery black powder.
[0034] The expression "battery black powder" is often used in the industry to describe an intermediate product derived from Li-ion batteries or their waste materials (such as new or spent Li-ion batteries, used or scrapped batteries, production or battery waste, electrode materials or other pre-treated battery materials). The batteries are usually disassembled. Thereby, for example, Al, Fe and Cu are separated from the casing and cables. All these battery materials are then shredded and sometimes pre-treated (for example by heat treatment) to remove residual electrolyte or graphite, thereby obtaining a powder or filter cake, which can be further processed into blocks or pellets. In the latter case, this may include mixing with other compounds that do not originate from Li-ion batteries or their waste materials to produce those blocks or pellets.
[0035] The battery black powder will still contain a considerable amount of Co and / or Ni, making the pyrometallurgical process economically viable. The above characteristics make the battery black powder a preferred feed material for the method.
[0036] The "major part" of an element or compound means: more than 50% by weight of the corresponding amount present in the feed. It can also include ranges having lower limits selected from 55%, 60%, 65%, 70% and 75% and upper limits selected from 80%, 85%, 90%, 95% and 100%.
[0037] According to another embodiment, the content of MnO in the slag is 30% or more, preferably 40% or more.
[0038] The content of MnO in the slag plays a key role in the present invention. At least 10% MnO is required in the slag to observe the effect of inhibiting the dissolution of MgO from the magnesium-containing refractory bricks of the furnace lining into the slag. At least 25% MnO in the slag fully shows the effect of inhibiting the dissolution of MgO. It is preferred that the slag has at least 30% MnO, more preferably at least 40%. When the method uses battery black powder as the starting feed and uses a minimum amount of slag-forming agent to save costs and keep the slag volume low, the amount of MnO in the slag will generally be higher than 25%.
[0039] Combining a MnO content of 25% to 70% with a relatively small volume of slag is beneficial as this is consistent with inhibiting MgO dissolution.
[0040] On the other hand, adding more flux, thereby increasing the overall volume of the slag and diluting the percentage of MnO to below 25%, gradually increases the amount of MgO dissolved from the refractory bricks, thus having a negative effect.
[0041] The upper limit of 70% MnO in the slag helps to keep the melting point of the slag sufficiently low.
[0042] Mn in the slag is denoted by "MnO". In such slags, the exact oxidation state of Mn is not always well defined. Thus, manganese oxide ("MnO") can also correspond to a mixture of MnO monoxide and MnO2 dioxide. It is assumed that the proportion of MnO is much higher than 95%, especially under the selected reduction reaction conditions.
[0043] MnO is usually green, while MnO2 is usually dark brown or dark gray, so it is called "manganese black". Green will only dominate when the content of monoxide is high enough.
[0044] The content of P2O5 in the slag is 0.5% <P2O5<10%。
[0045] Phosphorus usually originates from the electrolyte in Li-ion batteries and is incorporated into the slag in the form of P2O5.
[0046] Lithium iron phosphate (LFP) batteries typically contain more phosphorus than NMC batteries, but no cobalt and nickel. In an industrial setting, recyclers may have to process feed containing a mixture of such LFP batteries with NMC batteries, which would contribute to the overall phosphorus content of the slag.
[0047] According to another embodiment, the content of Al2O3 in the slag is less than 30%.
[0048] Too high a content of Al2O3, such as more than 30% or even more than 40%, increases the melting point of the slag. Heating to higher temperatures is less economically advantageous and increases refractory wear.
[0049] Battery black powder typically adds only limited amounts of Al2O3 to the slag. This is significantly different when starting with battery black powder rather than complete Li-ion batteries, which are typically rich in Al due to their outer shell.
[0050] The slag composition conforms to the formula Al2O3+0.5MnO<45%, allowing the slag to have a relatively high MnO content while limiting the amount of Al2O3.
[0051] According to another embodiment, the mass composition percentage of the slag is Al2O3+0.5MnO<30%. In this way, the amount of Al2O3 is further limited in the slag with a relatively high MnO content, which is beneficial to protecting the magnesia-containing refractory bricks.
[0052] According to another embodiment, the CaO content in the slag is 40% or less, preferably 30% or less.
[0053] CaO helps keep the slag sufficiently fluid and ensures that it is easy to handle. CaO also helps inhibit the dissolution of MgO from magnesia-containing refractory bricks, as Ca and Mg have similar chemical sites in the slag. Operating the process at the preferred upper limit of 30% CaO helps keep the melting point of the slag below 1600°C. However, too high amounts of CaO, such as above 40%, increase the melting point of the slag and should be avoided.
[0054] On the other hand, an increase in the amount of MnO allows a reduction in the amount of CaO since they are similar in suppressing the dissolution of MgO from the magnesia-containing refractory brick.
[0055] According to another embodiment, the slag forming agent does not contain CaO.
[0056] MnO-rich feeds even allow to completely avoid CaO as a slag former. This opens the way to explore other slag systems besides the well-known ternary slag system Al2O3-CaO-SiO2 commonly used in the prior art.
[0057] The beneficial effects of the present invention can still be achieved without CaO, since MnO in the slag plays a key role in this regard.
[0058] According to another embodiment, the Li2O content in the slag is greater than 3%, preferably greater than 6%.
[0059] It was also observed that, in addition to MnO and CaO, Li2O could also inhibit the dissolution of Mg from Mg-containing refractory bricks. When recycling Li-ion batteries, the amount of Li2O in the slag is expected to be large.
[0060] In this context, >3% is to be understood as meaning in particular 3.1 or more, preferably 3.2 or more, 3.3 or more, 3.4 or more, and in particular also 3.5 or more, 4.0 or more, 4.5 or more, 5.0 or more, 5.5 or more. Amounts greater than 3% allow for a valorization of the lithium in the slag. However, since Li2O also has an inhibitory effect on Mg dissolution, higher amounts (e.g. greater than 6%) are preferred not only for economic reasons but also because the contribution to wear reduction is greater. This is also particularly true for amounts of 7% or more, 8% or more, 9% or more, 10% or more.
[0061] SiO2 helps to lower the melting point of the slag. On the other hand, increasing the amount of SiO2 has a negative effect. Therefore, according to another embodiment, the amount of SiO2 in the slag is less than 20%.
[0062] In a preferred embodiment, the slag composition conforms to the formula (CaO+2Li2O+0.4MnO) / SiO2≥2.0.
[0063] According to another embodiment, the content of cobalt oxide in the slag is 0.05%. <CoO<1%。
[0064] Under the applied process conditions, most of the cobalt is incorporated into the alloy, while only a small part of the cobalt remains in the slag. Typically, concentrations of less than 1% are obtained. Completely cobalt-free slags cannot be obtained in industrial Li-ion battery recycling.
[0065] According to another embodiment, the Fe content in the slag is 25% or less, preferably 10% or less. In FeO-rich slags containing more than 10% FeO or even more than 25% FeO, CoO cannot be reduced to metallic Co without transferring relatively large amounts of metallic Fe into the alloy phase. This greatly increases the cost of any hydrometallurgical subsequent processing of the resulting alloy and is therefore less than ideal. In addition, Fe-containing slags are corrosive to magnesia-containing refractory bricks at high temperatures.
[0066] Therefore, according to a preferred embodiment, the Fe content in the feed is 5% or less. This can be achieved, for example, by separating the Fe-containing casing material, or by keeping the amount of undesirable lithium iron phosphate (LFP) batteries in the feed sufficiently low.
[0067] Slag composition and operating temperature are key considerations for the methods described herein. The present invention achieves a balance between compounds that protect the furnace walls (e.g., MnO, CaO, Li2O) and compounds that have a negative impact on the furnace walls. In addition, the slag composition domain allows the slag to have appropriate fluidity and minimal overheating of the slag at the desired operating temperature. It is preferred that the temperature be as low as possible while still remaining above the melting point of the alloy.
[0068] This balance is reflected in the proposed process conditions as well as in the composition of the slag itself.
[0069] According to another embodiment, the step of melting the feed is carried out at a temperature of at least 1400°C to ensure complete melting of the metallurgical feed and at most 300°C above the liquidus point of the slag, preferably at most 100°C above the liquidus point of the slag. The lower limit is preferred to avoid even partial solidification of the produced alloy or slag. The upper limit is preferred to avoid overheating the slag. Higher temperatures promote the dissolution of Mg from Mg-containing refractory bricks. Therefore, in order to reduce wear and save energy, lower temperatures are generally preferred. Overheating the slag has a negative impact on the dissolution of Mg-containing refractory bricks by the slag.
[0070] Preferred operating temperatures are below 1700°C, more preferably below 1650°C, even more preferably below 1600°C, most preferably below 1550°C.
[0071] According to another embodiment, the smelting step comprises the further steps of:
[0072] - Sampling of slag;
[0073] - cooling the slag sample and evaluating its color; and
[0074] - in case the slag sample is green, terminating the smelting step; or
[0075] - In case the slag sample is not green, the smelting step is continued after adjusting the pO2 level to achieve more reducing conditions.
[0076] "Sampling the slag" means removing a small sample of the slag while continuing the method under selected conditions.
[0077] The evaluation of color can be easily performed by visual inspection. Compared with chemical analysis of slag, monitoring color changes can quickly and effectively indicate that the slag contains a certain minimum percentage of MnO. As will be described in more detail below, it is further observed that the green color of the slag also indicates that most of the Co contained in the feed is reduced, thereby merging into the alloy. Without being bound by theory, it is actually believed that the color becomes green due to the reduction of MnO2 to MnO, but also due to the reduction of the usually darker oxides of Fe, Ni and Co, for example.
[0078] Visual inspection is a quick and easy method of process control that saves time and operating costs.
[0079] In the context of the present invention, "green" is defined as a color having a hue, lightness and chroma within the following ranges according to the ASTM D1535-14 (2018) standard:
[0080] - Tones range from 5GY to 5BG;
[0081] - Brightness: ≥3; and
[0082] - Chroma: ≥3.
[0083] An example of green is shown in the "Geological Rock Color Chart and Original Munsell Color Chart" produced by Munsell Color Company in 2009.
[0084] The operating conditions are selected so as to oxidize most of the Mn to slag and reduce most of the Co and Ni to alloy. Preferably more than 90%, more preferably more than 95%, most preferably more than 98% of the Co and Ni are collected in the alloy. The pO2 level of the process of the present invention is easily adjusted to achieve these favorable yields.
[0085] According to another embodiment, the pO2 level is adjusted to 10 -7 >pO2>10 -12 , preferably adjusted to pO2<10 -8 , preferably adjusted to pO2<10 -8.5 , preferably adjusted to pO2 < 10 -9 .
[0086] with 10 -7 Compared with the pO2 level of 10 -8 , 10 -8.5 and 10 -9 The preferred pO2 level and 10 -12 The limit of actually represents stronger reducing conditions and is conducive to high reduction yields.
[0087] According to another embodiment, the color of the slag is green. During smelting of the feed material under reducing conditions, the color of the slag typically changes from dark grey or dark brown to green as the process proceeds.
[0088] According to another embodiment, the furnace is an electric furnace. Using an electric furnace or electric arc furnace (EAF) allows greater flexibility in situations where higher operating temperatures are desired or required. Another advantage is that it allows benefiting from off-peak electricity prices, or electricity produced by environmentally friendly green sources such as local wind power plants.
[0089] Another embodiment describes a Li-containing metallurgical slag having the following weight percentage composition:
[0090] 25% <MnO<70%;
[0091] Al2O3+0.5MnO<45%;
[0092] SiO2>5%;
[0093] Li2O>3%;
[0094] 0.5% <P2O5<10%;
[0095] MnO+Li2O+Al2O3+CaO+SiO2+FeO+MgO+P2O5>90%; and
[0096] Among them, (CaO+2Li2O+0.4MnO) / SiO2≥2.0.
[0097] Another embodiment describes a Li-containing metallurgical slag, wherein the color of the slag is green. The green color indicates that the slag contains a certain minimum percentage of MnO, which is important for specific slag properties.
[0098] Another embodiment describes a Li-containing metallurgical slag, wherein the content of MnO in the slag is 30% or more, preferably 40% or more. A higher amount is beneficial to protect the furnace wall.
[0099] Another embodiment describes a Li-containing metallurgical slag, wherein the content of Al2O3 in the slag is less than 30%. Limiting the amount to less than 30% is beneficial to achieve a lower melting point.
[0100] Another embodiment describes a Li-containing metallurgical slag, wherein the CaO content in the slag is 40% or less, preferably 30% or less. Slags with relatively high amounts of MnO, such as over 40% or even over 50%, allow for low to very low CaO contents. This includes slags that do not contain CaO.
[0101] In all the above cases, the beneficial properties of the slag according to the invention of preventing wear or corrosion of the furnace walls or preventing the dissolution of MgO from magnesia-containing refractory bricks are maintained.
[0102] Another embodiment describes a Li-containing metallurgical slag, wherein the Fe content in the slag is 25% or less, preferably 10% or less. When the slag is reused in a new pyrometallurgical operation, the iron in the slag may be transferred to the alloy, which is undesirable because it makes any subsequent hydrometallurgical processing of the alloy more complicated and therefore costly.
[0103] Another embodiment describes the use of the Li-containing metallurgical slag as a slag-forming agent in a pyrometallurgical recovery process. The obtained metallurgical slag contains one or more of MnO, Al2O3, CaO and SiO2, and can therefore be used as a slag-forming agent in new operations.
[0104] Another embodiment describes the use of the Li-containing metallurgical slag as a slag-forming agent in the method according to the first embodiment, thereby partially or completely replacing the slag-forming agent in the step of providing a feed comprising the slag-forming agent.
[0105] The reuse of the produced metallurgical slag in new operations allows for more flexible selection of operating conditions, such as the pO2 level of the process. For example, when more oxidizing conditions are used, thereby sending more Co and / or Ni to the slag, these valuable metals will be recovered in subsequent operating cycles, where more reducing conditions can be used to recover more Co and / or Ni. Therefore, another embodiment describes a Li-containing metallurgical slag, wherein the slag also contains cobalt.
[0106] When the metallurgical slag is reused as a slag-forming agent in a new process cycle, it should be considered that the input batteries or their scrap may contain additional amounts of compounds such as Al, Mn or Li, which will eventually enter the slag after oxidation. As a result, the amount of Al2O3, MnO or Li2O in the slag will increase. In particular, Al2O3 has a direct influence on the melting point, so the accumulation in the slag needs to be monitored.
[0107] Due to the input of new compounds, the metallurgical slag according to the present invention can only be reused for a limited number of cycles. To determine whether the slag can continue to be reused, the slag composition should be analyzed and compared to the composition specifications described herein. Tapping and reusing at least a portion of the metallurgical slag, or diluting it with new slag-forming agents, is a viable long-term option.
[0108] As mentioned above, the slag according to the invention helps to significantly inhibit the dissolution of MgO from magnesia-containing refractory bricks. However, it cannot be completely avoided. This leads to another positive side effect when recycling the slag. Any MgO that has accumulated in the slag during previous smelting operations tends to inhibit further corrosion of refractory bricks when combined with MnO, Li2O and CaO. This makes reusing the slag particularly attractive.
[0109] Another embodiment describes the use of the Li-containing metallurgical slag in a lithium recovery process. Slags with a Li2O content of more than 3% allow the lithium contained to be increased in value, while higher Li2O contents, such as more than 6% or even more than 8%, are preferred. Lithium recovery is particularly attractive in cases where the slag is repeatedly reused, because each new cycle accumulates Li2O in the slag, easily reaching concentrations of more than 8%, more than 10%, more than 12% or more than 14%.
[0110] Li fuming is the preferred process for recovering lithium from such Li-containing metallurgical slags, as it ensures high recovery rates. For this purpose, the use of alkali or alkaline earth metal chlorides, such as CaCl2, has been described in WO2020104164.
[0111] Another embodiment describes the use of the Li-containing metallurgical slag in a cobalt recovery process. The reuse of the slag as a slagging agent in the method according to the first embodiment or other battery recycling processes allows the recovery of residual cobalt. This is not only for economic benefits, but also for ecological reasons.
[0112] The CoO in the slag will preferably be limited to less than 1%, more preferably less than 0.5%, thereby reducing the loss of this valuable metal and producing a slag that can be safely disposed of in a landfill once it is no longer used.
[0113] The following examples are provided to further illustrate embodiments of the present invention.
[0114] Example 1
[0115] The dissolution of MgO from the wall of a Mg-containing crucible was measured when using several different slag compositions. Various compounds contained in Li-ion batteries or their waste, respectively their oxides such as FeO, Al2O3, Li2O, MnO and P2O5, were melted in a 1 L MgO crucible together with CaO and SiO2 as fluxes. The total weight of the added oxides was 1000 g.
[0116] The crucible was gradually heated at a heating rate of 150°C / h using an induction furnace. When the slag was completely melted, the crucible was kept at a temperature of 1500°C or 1650°C. After heating for 2 hours, the molten slag was taken out of the crucible and quenched with water. Table 1 lists the composition of the slag produced in this example.
[0117] Table 1: Composition of the produced slag
[0118]
[0119] The MgO concentration in the above slag is relatively low. This result shows that under the selected conditions, the dissolution of MgO from the crucible wall is well suppressed.
[0120] (CaO+2Li2O+0.4MnO) / SiO2 is 2.9 in slag 1-1, 2.2 in slag 1-2, and 9.0 in slag 1-3.
[0121] Experiments were conducted with slag compositions containing no Ni, Co or Cu, since the amounts of these metals in the final slag are usually very low and therefore do not substantially affect the slag properties.
[0122] Comparative Example 2
[0123] The dissolution of MgO from the wall of a Mg-containing crucible was measured when using different slag compositions. Various compounds contained in Li-ion batteries or their waste, respectively their oxides such as FeO, Al2O3, Li2O, MnO and P2O5, were melted in a 1 L MgO crucible together with CaO and SiO2 as fluxes. The total weight of the added oxides was 1000 g.
[0124] The crucible was gradually heated at a heating rate of 150°C / h using an induction furnace. When the slag was completely melted, the crucible was kept at a temperature of 1500°C for 2 hours. After heating for 2 hours, the molten slag was taken out of the crucible and quenched with water. Table 2 lists the composition of the slag produced in this example.
[0125] Table 2: Composition of the produced slag
[0126]
[0127] Compared with the slag used in Example 1, the MnO content in the slag was adjusted to less than 10%. (CaO + 2Li2O + 0.4MnO) / SiO2 was 1.2 in slag 2-1 and 1.1 in slag 2-2. The measured MgO concentrations in the above slags were relatively high (9.0% to 15.7%), which indicates that a relatively large amount of MgO was dissolved from the crucible into the corresponding slag. As in Example 1, the slag did not contain Ni, Co or Cu.
[0128] Discussion of Example 1 and Example 2
[0129] The slag obtained in Example 1 contained less MgO than the slag obtained in Comparative Example 2. Under the conditions of Example 1, no significant degradation of the MgO crucible was observed, while under the conditions of Comparative Example 2, the crucible wall became thinner. As shown in Example 1, the slag containing a relatively high concentration of MnO suppressed the dissolution of MgO. More specifically, when the MnO concentration was 25% or more, the dissolution of MgO into the slag was effectively suppressed.
[0130] Example 3
[0131] 500 kg of battery black powder was charged to a 1 m diameter furnace newly lined with 200 mm chrome-magnesia refractory bricks. Slag produced in an earlier smelting operation and having the composition shown in Table 3 was added together with the battery black powder and reused as a slag forming agent. A bath temperature of 1500°C to 1550°C was maintained, which was suitable for maintaining sufficient fluidity of the slag and alloy for easy slagging and handling. Heat was provided by oxidizing the Al and C in the battery using submerged O2 injection. The injection rate was selected to achieve strong reducing conditions, i.e., pO2 of 10 in this case. -9Natural gas is added to compensate for heat losses in the furnace. After 1 hour of heating, the resulting alloy and slag are separated by tapping. During the process, small amounts of fuming material are captured.
[0132] Table 3 shows the analysis of the input and output phases of the method.
[0133] Table 3: Input and output phases of the described method
[0134]
[0135] During the battery processing, no significant degradation of the MgO-containing refractory bricks was observed. The concentration of MgO in the produced slag was only 1.4%, which was equivalent to a loss of 0.1 kg of MgO in the refractory bricks, which was a very small degradation, due to the high content of MnO in the slag. Therefore, this slag effectively suppressed the wear of the furnace wall made of MgO-containing refractory bricks.
[0136] General conclusions
[0137] The metallurgical slag according to the present invention is suitable for recovering valuable metals, such as Ni and Co, from Li-ion batteries or their waste, while minimizing the degradation of Mg-containing refractory bricks of the furnace.
Claims
1. A method for recovering Ni and Co from a Li-ion battery or its waste, the method comprising the following steps: - Providing a furnace lined with magnesia-containing refractory bricks; - providing a feed comprising a slag forming agent and Li-ion batteries or waste thereof, wherein the Al content of the feed is less than 8%; and - Smelting the feed material under reducing conditions to obtain an alloy containing a major portion of Ni and Co and a Li-containing slag, wherein the slag has the following composition percentages by weight: 25% <MnO<70%; Al2O3+0.5MnO<45%; SiO2>5%; Li2O>1%; 0.5% <P2O5<10%; MnO+Li2O+Al2O3+CaO+SiO2+FeO+MgO+P2O5>90%; and and Among them, (CaO+2Li2O+0.4MnO) / SiO2≥2.
0.
2. The method according to claim 1, wherein the content of MnO in the slag is 30% or more.
3. The method according to claim 1 or 2, wherein the content of Al2O3 in the slag is less than 30%.
4. The method according to any one of claims 1 to 3, wherein the Li-ion battery or waste material thereof is battery black powder.
5. The method according to any one of claims 1 to 4, wherein the content of CaO in the slag is 40% or less, preferably 30% or less.
6. The method according to any one of claims 1 to 5, wherein the content of Li2O in the slag is greater than 3%.
7. The method according to any one of claims 1 to 6, wherein the content of cobalt oxide in the slag is 0.05% <CoO<1%。 8. The method according to any one of claims 1 to 7, wherein the content of Fe in the slag is 25% or less, preferably 10% or less.
9. The method according to any one of claims 1 to 8, wherein the content of Fe in the feed is 5% or less.
10. The method according to any one of claims 1 to 9, wherein the step of smelting the feed material is carried out at a temperature of at least 1400°C and at most 300°C above the liquidus point of the slag, preferably at most 100°C above the liquidus point of the slag, thereby avoiding overheating.
11. The method according to any one of claims 1 to 10, wherein the smelting step comprises the further steps of: - taking samples of the slag; - cooling the slag sample and evaluating its color; and - in case the slag sample is green, terminating the smelting step; or - In case the slag sample is not green, the smelting step is continued after adjusting the pO2 level to achieve more reducing conditions.
12. The method according to any one of claims 1 to 11, wherein the pO2 level is adjusted to 10 -7 >pO2>10 -12 , preferably adjusted to pO2<10 -8 , preferably adjusted to pO2<10 -8.5 , preferably adjusted to pO2 < 10 -9 .
13. The method according to claim 11 or 12, wherein the color of the slag is green.
14. The method according to any one of claims 1 to 13, wherein the furnace is an electric furnace.
15. A Li-containing metallurgical slag, the weight composition percentage of which is as follows: 25% <MnO<70%; Al2O3+0.5MnO<45%; SiO2>5%; Li2O>3%; 0.5% <P2O5<10%; MnO+Li2O+Al2O3+CaO+SiO2+FeO+MgO+P2O5>90%; and and Among them, (CaO+2Li2O+0.4MnO) / SiO2≥2.
0.
16. The Li-containing metallurgical slag according to claim 15, wherein the color of the slag is green.
17. The Li-containing metallurgical slag according to claim 15 or 16, wherein the content of MnO in the slag is 30% or more, preferably 40% or more.
18. The Li-containing metallurgical slag according to any one of claims 15 to 17, wherein the content of Al2O3 in the slag is less than 30%.
19. The Li-containing metallurgical slag according to any one of claims 15 to 18, wherein the content of CaO in the slag is 40% or less, preferably 30% or less.
20. The Li-containing metallurgical slag according to any one of claims 15 to 19, wherein the content of Fe in the slag is 25% or less, preferably 10% or less.
21. Use of the Li-containing metallurgical slag according to any one of claims 15 to 20 as a slag-forming agent in a pyrometallurgical recovery process.
22. Use of the Li-containing metallurgical slag according to any one of claims 15 to 20 as a slag-forming agent in a method according to any one of claims 1 to 16, thereby partially or completely replacing the slag-forming agent in the step of providing a feed comprising the slag-forming agent.
23. Use of the Li-containing metallurgical slag according to any one of claims 15 to 20 in a lithium recovery process.
24. The Li-containing metallurgical slag according to any one of claims 15 to 20, wherein the slag further contains cobalt.
25. Use of the metallurgical slag according to claim 24 in a cobalt recovery process.
Citation Information
Patent Citations
Recycling method for Co- and / or Ni-containing waste battery
CN104674013A
Recovery treatment method for Mn containing waste batteries
CN104789778A
Process for recycling cobalt-bearing materials
CN110199038A
Recovery method and system for waste lithium-ion battery black powder
CN111118296A
Process for the recovery of lithium
CN113166846A
